A bottom-up evaluation on cryoprotective potentials of gelatine from fish scale. (March 2022) - Zhu, Shichen; Yu, Jiehang; Liu, Shulai; Ding, Yuting; Wang, Wenjie; Zhou, Xuxia
Abstract: The potential health risks and high cost of current cryoprotectants have emphasised the need to develop antifreezes with high safety and low expense. Gelatine is a promising alternative to these cryoprotectants due to its inherent structural attributes and high availability. In this study, the feasibility of three types of gelatines (gelatine A, B and P) as cryoprotectants in terms of the secondary structure and gel properties related to antifreeze performance was comprehensively investigated. Sodium dodecyl sulphate–polyacrylamide gel electrophoresis analysis patterns suggested that gelatine A had the lowest structural stability upon freeze–thaw (F–T) treatments, which was confirmed by the presence of low-molecular-weight fragments. The two-dimensional correlation infrared spectroscopy indicated that gelatine P had the greatest stability and highest sensitivity to F–T treatments according to changes in the polyproline type II helix structure. Gelatine B showed the lowest gel strength and viscosity compared with the two other gelatines when subjected to the same F–T cycles, which may be ascribed to the loose and inhomogeneous microstructure of gelatine B due to its impaired molecular structure. Gelatine P may be the promising antifreeze used for cryoprotection of the frozen food via the further modifications. This work may provide some valuable guidelines for the development of novel cryoprotectants from the perspective of bottom-up strategies. Graphical abstract: Image 1 Highlights: Gelatin A displays the poor structure stability upon F-T treatment. Gelatin B has the lowest gel strength and viscosity. Gelatin P shows the great stability and high sensibility to F-T treatment. Gelatin P is substrate for the further modifications for cryoprotection.